2020
DOI: 10.1039/c9sm02002k
|View full text |Cite
|
Sign up to set email alerts
|

The influence of confinement on the structure of colloidal systems with competing interactions

Abstract: Using grand canonical Monte Carlo simulations, we investigate how the structure of a colloidal fluid with competing interactions can be modified by confinement in channels with different cross-section geometries and sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…In the particular case of systems with competing interactions, previous theory and simulation studies showed that confinement can promote or inhibit the formation of periodic microphases depending on whether the pore size is commensurate or not with the periodicity of the bulk microphase. For example, we showed in a previous work that confinement in channels with triangular and hexagonal cross-sections favour the formation of the hexagonal phase, as well as by introducing wedges in pores with cylindrical crosssections (which otherwise promote the formation of helical structures) [25,26]. We also found that new phases that are not stable in bulk can be stabilised when confined by the appropriate pore geometry.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the particular case of systems with competing interactions, previous theory and simulation studies showed that confinement can promote or inhibit the formation of periodic microphases depending on whether the pore size is commensurate or not with the periodicity of the bulk microphase. For example, we showed in a previous work that confinement in channels with triangular and hexagonal cross-sections favour the formation of the hexagonal phase, as well as by introducing wedges in pores with cylindrical crosssections (which otherwise promote the formation of helical structures) [25,26]. We also found that new phases that are not stable in bulk can be stabilised when confined by the appropriate pore geometry.…”
Section: Introductionsupporting
confidence: 56%
“…Local density isosurfaces ρ * iso = 0.30 for all the ordered microphases obtained at different slit widths, W * . Note that the density chosen for the isosurfaces is somewhat lower than that in our previous work on SALR systems modelled with the square-well linear model (in which we chose ρ * iso = 0.40) [25][26][27]. The reason for this new choice is that the clusters obtained with the Lennard-Jones plus Yukawa model used in this work are appreciably smaller [17].…”
Section: Equilibrium Propertiesmentioning
confidence: 95%
“…14 In previous work, it has been shown that colloidal systems with competing interactions may be tuned by confinement to form exotic structures that are not present in bulk or to help the nucleation of periodic microphases that are stable in bulk according to theory and simulations but that remain experimentally elusive. [44][45][46][47] Thus, in the future, it would be also interesting to study the dynamics under confinement. We wonder if periodic microphases can be also made kinetically favoured (and not only thermodynamically) under the appropriate confinement conditions.…”
Section: Soft Mattermentioning
confidence: 99%
“…Based on the pH of our solution (pH ≈ 5.5), we find that the solution ionic strength is approximately I = 10 −5.5 = 3 × 10 −6 M. Therefore, the Debye length is expected to be κ −1 (nm) = 0.304/ √ I (M ) = 175 nm [73], in good agreement with the fit values of 100 to 230 nm that we obtained by fitting Eqs. (7) and (11) to the experimental data for both sphere and dumbbell particles, respectively. We neglected van der Waals interactions; we used the Derjaguin approximations for F e .…”
Section: F Sphere Height Distributionmentioning
confidence: 99%
“…Such particles often serve as model systems for understanding the effects of confinement on microscale processes, e.g., structure formation and rheology, offering quantitative insights into the behavior of biological systems [2][3][4]. This understanding is further desirable for various applications where confinement dictates the dynamics, ranging from improving microfluid transport in lab-on-a-chip devices [5], growing low-defect photonic crystals [6], and tuning pattern formation for materials design [7][8][9].…”
Section: Introductionmentioning
confidence: 99%